2010
DOI: 10.1177/0146167210362981
|View full text |Cite
|
Sign up to set email alerts
|

“Think” Versus “Feel” Framing Effects in Persuasion

Abstract: Three studies explored think ("I think . . . ") versus feel ("I feel . . . ") message framing effects on persuasion.The authors propose a matching hypothesis, suggesting that think framing will be more persuasive when the target attitude or message recipient is cognitively oriented, whereas feel framing will be more persuasive when the target attitude or message recipient is affectively oriented. Study 1 presented cognitively and affectively oriented individuals with a think- or feel-framed message. Study 2 pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
126
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(139 citation statements)
references
References 45 publications
10
126
2
1
Order By: Relevance
“…Prior works have shown that product category (Johar and Sirgy 1991), consumer trait (Fabrigar and Petty 1999;See et al 2008), and message framing (Mayer and Tormala 2010) could moderate these effects. This article demonstrates that construal level moderates these effects as well.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Prior works have shown that product category (Johar and Sirgy 1991), consumer trait (Fabrigar and Petty 1999;See et al 2008), and message framing (Mayer and Tormala 2010) could moderate these effects. This article demonstrates that construal level moderates these effects as well.…”
Section: Discussionmentioning
confidence: 98%
“…In fact, a mere perception concerning one's attitude could influence one's interest for affective-or cognitive-related information (See et al 2008). Finally, different message framing (e.g., "I feel…" vs. "I think…") could also influence the persuasion effectiveness such that feel (vs. think) framing is more persuasive for consumers who are affectively (vs. cognitively) oriented (Mayer and Tormala 2010).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Aristotle proposed three modes of persuasion: pathos (appealing to the target's emotions), logos (applying a logical argument), and ethos (affect of the 'persuader's' perceived authority) [40,41]. There is evidence for the importance of emotion and logic in the formation of opinion [42,43]. Indeed, it has been argued that all three are present in any effective form of persuasive discourse [41].…”
Section: Modeling Authoritymentioning
confidence: 99%
“…In certain forms (e.g., I feel) the word feel represents a disclosing speech act with closer association to inner emotional experiences than other more cognitively symbolic representatives like the words think or believe (Fiehler, 2002;Mayer & Tormala, 2010). In fact, Mayer & Tormala (2010) determined that feel and think leave distinctly different impressions on the listener. Due to its emotional connotation, it is presumed that feel does not align itself with the rational-professional discourse.…”
Section: Emotional Expression and The Workplacementioning
confidence: 99%